Dynamics of a prototype alkali-hydrogen-halide exchange reaction on an ab initio potential-energy surface - Ibrahim Ali , Noorbatcha (Elsevier Ltd., 1984)
We report the results of a quasiclassical trajectory (QCT) study of a prototype alkali-hydrogen-halide exchange reaction Li + FH → LiF + H on an ab initio potential-energy surface for collinear as well as non-collinear geometries. A vibrational threshold equal to that of the barrier (21 kcal mol−1) noted for the collinear collisions is not found for the 3D collisions. Nevertheless, we do find that vibrational energy (V) is much more efficient than translational energy (T) in causing this reaction. There is a unique effect of reagent rotation on the reaction cross section (Sr) in that with increase in the rotational quantum number (J) from 0 through 15 for the vibrational state ν = 2 at T = 8.7 kcal mol−l, Sr decreases initially and then increases steeply. This is followed by a decline and a possible levelling off in St. We attribute the initial decline in Sr(J) to the disruption of the preferred alignment due to rotation. Further increase in rotation brings the molecule back into alignment and with much more rotational velocity, the molecule appears as a blur explaining the levelling off of Sr. Interestingly, for ν = 0, there is a moderate rotational enhancement partly due to the increase in the number of product states becoming available with increase in the total energy. The effect of various forms of energy on other reaction attributes like product vibrational- and rotational-energy distribution and angular distribution has also been studied. Our calculated value of Sr as well as the product angular distribution and the coplanarity of the reaction are in good agreement with the exerimental results for ν = 0, but they differ significantly from the QCT results of Shapiro and co-workers on their semi-empirical PES.